LEGAL PROTECTION FOR CONSUMERS IN ONLINE BUYING AND SALES TRANSACTIONS RELATED TO NON-CONFORMITY OF GOODS OFFERED - Mudawaroh (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
This research was conducted with the aim of knowing the legal issues based on Law No. 8 of 1999, Therefore, From Shopee user reviews it is known that the Shopee application still needs to be improved. For this reason, research was conducted to see public satisfaction with the Shopee application through the e-service quality method. goods purchased by consumers do not reach their hands and are sold conventionally (face-to-face). Consumers are often the subject of losses from online trading activities when the products received by consumers are not as ordered, delays in receiving products and non-delivery of products that have been ordered by consumers. The question that arises then is whether these provisions can apply universally to all cases, or only in certain cases that can create a sense of justice for the parties, With the formulation of the problem how to know the Legal Protection for consumers in online buying and selling transactions related to the Non-conformity of goods offered based on Law Number 8 of 1999 concerning Consumer Protection and how to know the legal consequences if business actors send goods that do not match the specifications of the goods offered in Online Buying and Selling. This study uses an empirical juridical method, namely by examining this research from primary data where data can be obtained directly from the first source through primary data acquisition, namely from field data that can be done through observation, observation, (interviews), or distributing questionnaires. In this study the author uses a statutory approach. The statutory approach is an approach carried out by analyzing rules and regulations related to legal issues. With the aim of getting answers to the problems raised with the conclusion of the use of rules applied in Law Number 8 of 1999 concerning Consumer Protection, legal protection is included in Article 7 paragraphs a, b, c, d. However, for consumers in South Jakarta City, it is not running effectively. Existing laws are not able to protect consumers as they should. Several consumers have filed complaints to demand compensation or redress, but business actors often ignore these complaints and are not responsible. As a result, the legal protection expected by consumers in South Jakarta City cannot be fulfilled.